Regional-scale analysis of arbuscular mycorrhizal fungi: the case of Burgundy vineyards - Bouffaud, Marie-Lara; Bernaud, Eric; Colombet, Annie; Van Tuinen, Diederik; Wipf, Daniel; Redecker, Dirk (OENO one, 2016)
Aim: To improve knowledge of arbuscular fungal communities for a sustainable management in vineyards. Methods and results: In 16 plots across Burgundy under contrasted soil properties and agricultural practices, we assessed arbuscular mycorrhizal fungal (AMF) diversity in vine roots, using pyrosequencing of ribosomal Internal Transcribed Spacers (ITS). AMF sequences could be retrieved from all plots across Burgundy, both in organic and in conventional vineyards with high chemical inputs. Sequences from the survey were almost exclusively affiliated to molecular taxa in the Glomerales, including six “core species” found in all plots, corresponding to 77% of all sequences, suggesting a relatively low species diversity in vine roots. A large part of the molecular taxa had no close similarity to previously-reported sequences. Conclusion: AMF diversity observed in vine roots was relatively low and a significant proportion of molecular taxa shared between the sites. Nevertheless, some differences in the AMF community composition were observed between the plots. Significance and impact of the study: This is the first large-scale study of AMF diversity in French vineyards using high-throughput sequencing, which will contribute to a better understanding of ecology of these fungi in vine roots, thus providing essential knowledge for future applications in sustainable agriculture in vineyards